Financial Integration and European Tourism Stocks - Guglielmo Maria Caporale; Stavroula Yfanti; Menelaos Karanasos; Jiaying Wu (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study examines the macro drivers of the time-varying (dynamic) connectedness between eleven European tourism sectors. Financial integration between the travel and leisure markets, measured by their dynamic correlations or co-movement, is explained by common global fundamentals. The empirical results provide new evidence on the counter-cyclical behaviour of the correlations; in particular, stronger cross-country interdependence can be attributed to economic slowdowns characterized by higher uncertainty and geopolitical risk, tighter credit and liquidity conditions, and sluggish economic and real estate activity. Further, economic and political uncertainty is found to intensify the macro effects on tourism correlations. Finally, crises such as the 2008 financial turmoil, the subsequent European debt crisis, and the recent Covid-19 pandemic crash, also magnify the impact of macro drivers on the evolution of co-movement and integration in the tourism sector.
Keywords: C32; D80; G01; L83; Z39; 330; cross-country tourism correlations; economic policy uncertainty; financial/health crisis; financial integration; sectoral contagion; travel and leisure industry